The Effect of Pelvic Floor Muscle Exercises on Urinary Incontinence and Leisure Time Activities of Women With Multiple Sclerosis - Seyed Mohammad Sadegh Hosseini; Mohammad Hadi Rostami; Mahsa Bakhtiari; Alireza Soltanian; Sahar Nurani Gharaborghe (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective This study seeks to explore the effects of pelvic floor muscle exercises on urinary incontinence and leisure time in women diagnosed with multiple sclerosis (MS). Materials & Methods A quasi-experimental design was utilized in this study. The research included 15 women with MS at stages 7 or lower on the expanded disability status scale, selected conveniently to form the intervention group. This group underwent a structured pelvic floor muscle exercise program. Pre-test and post-test assessments were conducted using the international consultation on incontinence questionnaire-urinary incontinence short form, the leisure activities questionnaire and the fatigue severity scale. The impact of the intervention was analyzed using the Wilcoxon test. Results The results demonstrated a significant reduction in urinary incontinence (P=0.007) and increased leisure activities (P=0.003) among women with MS who engaged in pelvic floor muscle exercises. However, these exercises did not significantly affect the participants' fatigue levels. Conclusion The study suggests pelvic floor exercises can effectively decrease urinary incontinence and enhance leisure activities in women with MS. These findings emphasize the importance of incorporating targeted exercises into the care of this patient population, providing valuable insights for healthcare professionals and individuals aiming to enhance their quality of life (QoL). Further research and integration of pelvic floor exercises into comprehensive care strategies are recommended to optimize the well-being of women with MS.